Optimization of Butanol Production from Mixed Sugars and Sweet Sorghum Bagasse Hydrolysate Using Clostridium beijerinckii TISTR 1461 - Chalida Daengbussadee; Lakkana Laopaiboon; Thanawat Thanapornsin; Pattana Laopaiboon (Energies)
This study investigated the capability of Clostridium beijerinckii TISTR 1461 to utilize mixed sugars (glucose and xylose) in synthetic media and sweet sorghum bagasse (SSB) hydrolysate for butanol production. Synthetic media containing 60 g/L of glucose and xylose at various ratios were used for butanol production. C. beijerinckii TISTR 1461 preferentially utilized glucose over xylose for butanol production. The highest butanol concentration (PB, 10.25–10.60 g/L), butanol yield (YB/S, 0.27–0.28 g/g), butanol productivity (QB, 0.22 g/L·h), and sugar consumption (SC, 61–63%) were achieved when the glucose content was at least 75% of the total sugars. When an SSB hydrolysate (produced via enzymatic hydrolysis) containing 60.83 g/L of total sugars (glucose:xylose ratio = 88:12, w/w) was used as a substrate for butanol production, the SSB hydrolysate supplemented with 1 g/L of yeast extract and buffers significantly yielded higher PB (15.10 g/L), YB/S (0.31 g/g), QB (0.31 g/L·h), and SC (82%) values compared to the synthetic media. These results indicate that sweet sorghum bagasse hydrolysates containing glucose and xylose mixtures show promise as cost-effective substrates for sustainable butanol fermentation, demonstrating the potential of agricultural residues in biofuel production.